ANALISIS KREATIVITAS SISWA DALAM KODING DAN KECERDASAN ARTIFISIAL (KKA) PADA MATERI SISTEM EKSKRESI MANUSIA DI SMP NEGERI 3 SURABAYA - Moh. Fikri Fahrudin; Fasih Bintang Ilhami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students' creativity in Coding and Artificial Intelligence (CAI) learning on the topic of the Human Excretory System at SMP Negeri 3 Surabaya. This research employs a quantitative approach with a pre-experimental design of the One Shot Case Study type. The subjects were 33 students of class VIII H. The learning treatment applied was the Cooperative Learning model of the Student Teams Achievement Division (STAD) type, in which students worked in groups during the learning process but individually created their own HTML website about the Human Excretory System assisted by Artificial Intelligence (AI). Creativity was assessed using four Torrance indicators: fluency, flexibility, originality, and elaboration. The results showed that all four aspects were in the creative to very creative category. Fluency achieved the highest average (85.61), followed by flexibility (81.06), elaboration (79.55), and originality as the lowest (66.67). Although CAI-integrated learning effectively stimulated students' idea productivity, flexibility, and elaboration, the originality aspect requires further attention due to the tendency of students to adopt AI outputs without significant modification. It is recommended that future learning designs incorporate an independent brainstorming phase prior to AI use to optimally and proportionally develop all dimensions of student creativity.